DESIGNING E-READING MATERIAL FOR THE FIRST GRADE OF SENIOR HIGH STUDENTS - Nurul Afidah (LPPM Universitas KH.A.Wahab Hasbullah Jombang, 2020)
ABSTRACT The purpose of this study is designing electronic-based materials of reading comprehension skill for the second semester at the first grade students of senior high school. It can be categorized as the Research and Development (R&D) which adapted the model of Sadiman (1986). It was consisted of seven phases such as(1) need analysis, (2) formulating objective, (3) formulating the materials, (4) formulating validity measurement, (5) writing media sheets, (6) testing, and (7) revising. The subjects were the first grade students of MAN Malang I. The product was developed based on the students and teachers’ need which was obtained from distributed questionnaire and interview, and it showed that both students and teacher need an interactive English instructional media which is based on computer with the percentage (92.3%). Furthermore, based on the validation of some experts, it was known that the product was valid. Finally, the result product was electronic-based materials which was consisted the reading materials of the second semester of the first grade of senior high school such as narrative, descriptive, and news item texts. Each kind of text has its own evaluation which is in the form of multiple choices and true or false questions. KEYWORDS: Electronic-Based Materials, Reading Comprehension, Reading Material